2014
DOI: 10.1007/s13193-014-0311-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Frozen Section in Intraoperative Assessment of Ovarian Masses: a Tertiary Oncology Center Experience.

Abstract: Surgical management of ovarian lesions vary considerably depending on the nature of the lesion. As the preoperative imaging and serum tumor marker levels are of limited value in the proper categorization of ovarian lesions, intraoperative pathological assessment is commonly requested for a primary diagnosis. Aim of the study is to assess the accuracy of the frozen section in the diagnosis of ovarian masses in our center and to analyze the causes of diagnostic discrepancies. In this retrospective study, frozen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
(20 reference statements)
2
12
0
Order By: Relevance
“…Given the low accuracy rate for borderline ovarian tumors, care and attention are required to develop this field (10,11,13,14,18). Most studies typically reported a sensitivity of 71-100% for the detection of malignancies by frozen section, and a specificity ranging from 96-100% (11,19,21,23,26,27). In our study, the sensitivity of malignant ovarian tumor detection was 93.3% and the specificity was 100%, reflecting that the frozen section examination was highly sensitive and specific to ovarian malignancy.…”
Section: Discussionsupporting
confidence: 55%
“…Given the low accuracy rate for borderline ovarian tumors, care and attention are required to develop this field (10,11,13,14,18). Most studies typically reported a sensitivity of 71-100% for the detection of malignancies by frozen section, and a specificity ranging from 96-100% (11,19,21,23,26,27). In our study, the sensitivity of malignant ovarian tumor detection was 93.3% and the specificity was 100%, reflecting that the frozen section examination was highly sensitive and specific to ovarian malignancy.…”
Section: Discussionsupporting
confidence: 55%
“…The relative sensitivities were 99.2, 88.46, and 82.95 %, respectively, for benign, borderline, and malignant tumors. There were 18 false negative diagnoses; most of them belonged to the borderline group [ 10 ]. A few authors specifically focused on borderline ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The overall accuracy in our study is 81.7%, this value is less than other values in previous studies which range from (90% to 97%) [1] [6]- [8] but still accepted. The overall accuracy which had shown in previous studies was 93.8% [8], 95.5% [1], 91.85% in [9], 97.1% [5] and this variation may be attributed to our small sample size and the raised age of cases. The sensitivity of benign, borderline and malignant ovarian tumors found 100%, 100% and 75.32%, respectively ( Table 3), and the specificity was for benign, borderline and malignant 82%, 95.19% and 100%, respectively which correlate with previous studies [1] [6]- [8].…”
Section: Discussionmentioning
confidence: 64%